Persistent reduction of Bifidobacterium longum in the infant gut microbiome in the first year of age following intrapartum penicillin prophylaxis for maternal GBS colonization - Teuscher, Jana Lucia; Lupatsii, Mariia; Graspeuntner, Simon; Jonassen, Sinje; Bringewatt, Arne; Herting, Egbert; Stichtenoth, Guido; Bossung, Verena; Rupp, Jan; Härtel, Christoph; Demmert, Martin (Frontiers in Immunology, 2025)
IntroductionGroup B Streptococcus is a significant cause of early-onset disease in term newborns, with a global incidence of 0.41/1000 live births. Intrapartum antibiotic prophylaxis (IAP) has reduced EOD incidence by over 80%, but concerns exist about its impact on the neonatal gut microbiome and potential long-term health effects.MethodsThis single center study examines the effects of IAP on the fecal infant microbiome in the first year of age and on the T cell phenotype in the first days after birth among 22 infants receiving IAP with penicillin due to maternal GBS colonization and 26 infants not exposed to IAP. The fecal microbiome was analyzed at birth, one month and one year of age through 16S rRNA gene sequencing. Additionally, a T cell phenotyping of peripheral blood was performed between the second and fifth day of age.ResultsAt one month, IAP exposed infants had a significantly lower relative abundance of Bifidobacterium longum in fecal samples, an effect which was sustained at one year. In IAP exposed infants we found a proinflammatory T-helper cell profile, characterized by higher IL-17A, RORgt, and TGF-b expression.DiscussionThis study proposes a sustained impact of IAP on the neonatal microbiome and T cell repertoire.